Tahfidz Al-Quran Learning Management - Fitri Handayani (Green Publisher Indonesia, 2021)
TAAM QUBA is a Muslim childcare park that has an integrated educational concept in which there are PG and Kindergarten with a focus on the Tahfidz Al Quran program. The problem in the tahfidz program lies in the learning process, seen from the underdevelopment of the methods used in the management of Tahfidz Al Quran learning including Planning, Implementation, Organizing including the role of the teacher and monitoring or evaluating learning. The purpose of this study is to analyze and describe planning, implementation, The Role of Supervisory Teachers and Learning Evaluation of Tahfiz Al Quran in TAAM QUBA Lumajang. This research method uses a descriptive-qualitative approach through interview, observation, documentation and document study or copying techniques. The results of this study concluded that, the implementation of Tahfiz Al Quran Learning at TAAM QUBA Lumajang, is strongly driven by the policies of the TAAM leadership and is supported by a solid team from the Deputy Head of TAAM, administrative staff and tutors. Learning Tahfiz Al Quran is carried out using the Wahdah, plural and Sima'i methods. Supervising teachers have not introduced other methods to students in learning Tahfiz Al Quran. In its implementation, Tahfiz Al-Quran Learning does not interfere / take up students' time to learn other aspects of development, and does not reduce students' academic achievement, and does not hinder students' activities from other activities.